Develpment platform for electrical management in Volvo Cars - Sundström, Stefan; Johnsson, Henrik (My University, 2007)
This master thesis examines the requirement for the implementation of an operational development platform for in-car electrical energy management. It has its starting point in the growing demands on the automotive battery, and the desire of the Department of Power Supply System at Volvo Cars for a test and evaluation platform for energy management algorithms and ideas. Focus is on battery status detection methods, conditions for integrating the platform with the present power supply system in a typical Volvo car, and on platform hardware and software possibilities and restrictions. Further, a user guide for such a platform is developed and evaluated. A battery state of charge calculation model is created in Simulink. The model is designed for implementation in a test car and configured for execution on the development platform. The process of generating executable code from the model is described and documented for easy use. In order to establish the accuracy of the model it is tested and evaluated compared to a reference model using battery data recorded in real car tests. Compared to the reference model, test results show that the Simulink model is acceptable for determining battery state of charge. However, no data is available for the true battery state of charge value from the real car test. Therefore a true comparison can not be done. A requirement for a fully operational development platform is the implementation of a communication interface between the platform and the Simulink model, handling the input and output signals. Proposed solutions for this problem is either the implementation of an underlying operating system on the platform, or the development of signal handling blocks directly in Simulink.
Keywords: Elkraftteknik; Electric power engineering